Post-cracking behaviour of selfcompacting steel fibre reinforced concrete - Pereira, E. N. B. (2004)
Self-compacting concrete (SCC) can be defined as concrete that is able to flow in the interior of the formwork, passing through the reinforcement and filling it in a natural manner, being consolidated under the action of its own weight. Adding the benefits of SCC to those resulting from the addition of discrete fibres to cement based materials, a high performance material, designated by steel fibre reinforced self-compacting concrete (SFRSCC), is obtained. In the present work the strategy followed to design SFRSCC is described, as well as, the experimental research carried out to characterize its flexural and compression behaviour. A special effort is done to assess the post-cracking behaviour, carrying out three point notched beam tests. The equivalent and the residual flexural tensile strength parameters, proposed by RILEM TC 162-TDF to characterize the toughness of steel fibre reinforced concrete (SFRC), are determined. To evaluate the stress-crack opening diagram of the designed SFRSCC, an inverse analysis is performed fitting the obtained experimental force-deflection curves.